Advances in the treatment of Adamantinomatous craniopharyngioma: How to balance tumor control and quality of life in the current environment: a narrative review - Chen, Ao; Ai, MingDa; Sun, Tao (Frontiers in Oncology, 2023)
Adamantinomatous craniopharyngioma (ACP) presents a significant challenge to neurosurgeons despite its benign histology due to its aggressive behavior and unique growth patterns. This narrative review explores the evolving landscape of ACP treatments and their efficacy, highlighting the continuous development in therapeutic approaches in recent years. Traditionally, complete resection was the primary treatment for ACP, but surgical -related morbidity have led to a shift. The invasive nature of the finger-like protrusions in the histological structure results in a higher recurrence rate for ACP compared to papillary craniopharyngioma (PCP), even after complete macroscopic resection. Given this, combining subtotal resection with adjuvant radiotherapy has shown potential for achieving similar tumor control rates and potentially positive endocrine effects. Simultaneously, adjuvant treatments (such as radiotherapy, intracystic treatment, and catheter implantation) following limited surgery offer alternative approaches for sustained disease control while minimizing morbidity and alleviating clinical symptoms. Additionally, advances in understanding the molecular pathways of ACP have paved the way for targeted drugs, showing promise for therapy. There is a diversity of treatment models for ACP, and determining the optimal approach remains a subject of ongoing debate in the present context. In order to achieve a good-term quality of life (QOL), the main goal of the cyst disappearance or reduction of surgical treatment is still the main. Additionally, there should be a greater emphasis on personalized treatment at this particular stage and the consideration of ACP as a potentially chronic neurosurgical condition. This review navigates the evolving landscape of ACP therapies, fostering ongoing discussions in this complex field.